Bis[1,2-bis-(diphenyl-phosphino)ethane-κP:P']silver(I) bis-(chloro-difluoro-acetato-κO)(4-chloro-phen-yl)diphenyl-stannate(IV). - Teo, Y.Y.; Lo, K.M.; Ng, Seik Weng (International Union of Crystallography, 2008)
In the title salt, [Ag(C(26)H(24)P(2))(2)][Sn(C(2)ClF(2)O(2))(2)(C(6)H(5))(2)(C(6)H(4)Cl)], the Ag(I) atom has a tetra-hedral and the Sn(IV) atom a trans-trigonal-bipyramidal coordination geometry. In the anion, the chloro substituent is disordered over two rings (occupancy ratio 0.81:0.19); the two chloro-difluoro-methyl groups are also disordered over two sites for their halogen atoms (occupancy ratios 0.72:0.28 and 0.70:0.30).